Numerical Study of the Magnetic Field Effects on the Heat Transfer and Entropy Generation Aspects of a Power Law Fluid over an Axisymmetric Stretching Plate Structure - Hooshmand, Payam; Gatabi, Hamed Rajabzadeh; Bagheri, Navid; Pirzadeh, Isma'il; Hesabi, Ashkan; Jamalabadi, Mohammad Yaghoub Abdollahzadeh; Oveisi, Majid (Mdpi, 2017)
Numerical investigation of the effects of magnetic field strength, thermal radiation, Joule heating, and viscous heating on a forced convective flow of a non-Newtonian, incompressible power law fluid in an axisymmetric stretching sheet with variable temperature wall is accomplished. The power law shear thinning viscosity-shear rate model for the anisotropic solutions and the Rosseland approximation for the thermal radiation through a highly absorbing medium are considered. The temperature dependent heat sources, Joule heating, and viscous heating are considered as the source terms in the energy balance. The non-dimensional boundary layer equations are solved numerically in terms of similarity variable. A parameter study on the Nusselt number, viscous components of entropy generation, and thermal components of entropy generation in fluid is performed as a function of thermal radiation parameter (0 to 2), Brinkman number (0 to 10), Prandtl number (0 to 10), Hartmann number (0 to 1), power law index (0 to 1), and heat source coefficient (0 to 0.1).
Keywords: thermal radiation; forced convection; entropy generation; viscous dissipation; power law; stretching sheet